The Use of urea Crystallization Method for The Preparation of ï·-3 Fatty Acids Concentrate from fish oils: A Review - Estiasih, Teti (Fakultas Teknologi Pertanian Universitas Brawijaya, 2006)
Some species of fish are known to be potential source of w-3 fatty acid, one of the essential fatty acids from human body. However, in many cases, the concentration of such fatty acids in the fish oil is quite low, and therefore, a method is needed to make it into a concentrate. One of the methods widely use is urea crystallization technique. Principally, this method is based on the inability of urea to form a complex with w-3 fatty acid, while other fractions are precipitated. This method is claimed to be able to increase w-3 fatty acids content up to 80%. Factors that influence the technique are temperature, crystallization time, and urea to oil ratio. An optimation of processing parameters for particular type of fish oil must be defined to obtain a high w-3 fatty acid concentrate. Â Keywords: w-3 fatty acid, concentrate, urea crystallization